Analisis Hadis Tematik Tentang Musyawarah (Syura) dan Implementasinya dalam Demokrasi Kontemporer - Sherly Widya Hapitasari; Muhammad Alif; Hikmatul Luthfi (STAI Nurul Qadim, 2025)
The idea of deliberation taught in Islamic teachings is a fundamental principle in the collective decision-making process that prioritizes the values of justice, equality, involvement, and common welfare. The Prophet Muhammad PBUH gave a real example in implementing shur, which is involving the companions to discuss and consider opinions in solving important problems, both in the social, political, and social fields. The values contained in the deliberations actually have a very close wedge with the principles of modern democracy, which uphold public participation, transparency, and shared responsibility in realizing the welfare of the community. Therefore, this study aims to examine the hadiths that discuss the concept of deliberation and analyze how it is relevant and applied in contemporary democratic practice. Using a qualitative thematic analysis approach, this study identifies and collects a number of hadiths related to deliberation, then examines the values contained in them, such as community involvement, representative systems, and public accountability. The results of this research are expected to be able to enrich scientific treasures while contributing to strengthening the values of deliberation in the context of modern democracy, so that the principles of shura that have been exemplified by the Prophet Muhammad PBUH remain relevant and able to be implemented in the system of government and community life in the current era. Thus, this study also opens up opportunities for the development of discourse on the integration of Islamic values with the democratic system as a foothold for building a just governance